Research Informed Science Enrichment Programs at the Gravity Discovery Centre. - Venville, G.; Blair, D.; Coward, D.; Deshon, F.; Gargano, M.; Gondwe, M.; Heary, A.; Longnecker, N.; Pitts, M.; Zadnik, Marjan (Australian Science Teachers Association, 2012)
Excursions to museums and science centres generally are great fun for students and teachers. The potential educational benefits beyond enjoyment, however, are rarely realised or analysed for their efficacy. The purpose of this paper is to describe four educational enrichment programs delivered at the Gravity Discovery Centre (GDC), near Gingin, Western Australia, that are informed by research in different ways. These programs are designed to maximise the educational outcomes for students, assess what they have learnt, and, at the same time, maintain the excitement and enthusiasm generated by a visit to a world class science centre.